2011
DOI: 10.1007/s00198-011-1790-z
|View full text |Cite
|
Sign up to set email alerts
|

Lactation is associated with greater maternal bone size and bone strength later in life

Abstract: Breastfeeding is beneficial to maternal bone strength in the long run.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 42 publications
4
37
0
Order By: Relevance
“…18 In a recent study, Wiklund et al displayed the protective effect of lactation on bone size and strength in direct correlation with its duration while Yazici et al found no effect of lactation and its duration on postmenopausal women. 19,20 Kauppi et al also confirmed the positive effect of parity on BMD and showed inverse association between risk of hip fracture and parity. 21 Moller et al concluded in their study that pregnancy and breastfeeding cause a reversible bone loss.…”
Section: Discussionmentioning
confidence: 88%
“…18 In a recent study, Wiklund et al displayed the protective effect of lactation on bone size and strength in direct correlation with its duration while Yazici et al found no effect of lactation and its duration on postmenopausal women. 19,20 Kauppi et al also confirmed the positive effect of parity on BMD and showed inverse association between risk of hip fracture and parity. 21 Moller et al concluded in their study that pregnancy and breastfeeding cause a reversible bone loss.…”
Section: Discussionmentioning
confidence: 88%
“…Concerning type of feeding: The highest percentage (60%) of the study sample was breast & bottle feeding as shown in table (2). Studies reported that history of breastfeeding affects bone mineral density and fracture risk later in life (23,24). While other study show that postmenopausal women with a history of breastfeeding had higher bone mineral density in the lumbar spine (25).…”
Section: Discussionmentioning
confidence: 93%
“…The highest percentage (30%) of the study sample their age were (20)(21)(22)(23)(24) year at first breastfeeding with mean and SD 23.17 ± 6.87as shown in Table (2). In cross-sectional study performed in postmenopausal women reported that there was a significantly lower incidence of osteoporosis among women who first breastfed at age after 27 years (21).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Cure-Cure and Cure [1] have raised the important question of whether greater maternal bone size and bone strength due to prolonged lactation protects women from fragility fractures in the long run. We cannot answer this question at this time since the majority of the women in our study [2] were pre-menopausal. We will explore this issue later by following up this cohort.…”
mentioning
confidence: 84%